1996
DOI: 10.1128/jvi.70.11.8081-8088.1996
|View full text |Cite
|
Sign up to set email alerts
|

Virus-specific interaction between the human cytomegalovirus major capsid protein and the C terminus of the assembly protein precursor

Abstract: We previously identified a minimal 12-amino-acid domain in the C terminus of the herpes simplex virus type 1 (HSV-1) scaffolding protein which is required for interaction with the HSV-1 major capsid protein. An ␣-helical structure which maximizes the hydropathicity of the minimal domain is required for the interaction. To address whether cytomegalovirus (CMV) utilizes the same strategy for capsid assembly, several glutathione S-transferase fusion proteins to the C terminus of the CMV assembly protein precursor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…6) (37). A similar study done with the HCMV pAP has identified a 16-aminoacid sequence within the CCD that promotes interaction of its GST fusion protein with the HCMV MCP (7). The biological importance of these carboxy-terminal domains was demonstrated by the finding that capsid formation was perturbed, both in the recombinant baculovirus HSV capsid assembly system (42,79) and in mutant HSV-infected cells (49), when the mature form of the protein (without tail) was used in place of the precursor (with tail).…”
Section: Discussionmentioning
confidence: 88%
“…6) (37). A similar study done with the HCMV pAP has identified a 16-aminoacid sequence within the CCD that promotes interaction of its GST fusion protein with the HCMV MCP (7). The biological importance of these carboxy-terminal domains was demonstrated by the finding that capsid formation was perturbed, both in the recombinant baculovirus HSV capsid assembly system (42,79) and in mutant HSV-infected cells (49), when the mature form of the protein (without tail) was used in place of the precursor (with tail).…”
Section: Discussionmentioning
confidence: 88%
“…Weigele, L. Sampson & S. C., unpublished results). Little is known concerning the functional domain structure of any other viral scaffolding proteins, except that herpesvirus scaffolding proteins' coat protein-binding sites are also about 25 amino acid a-helical regions which reside near the C termini of those proteins (Beaudet-Miller et al, 1996;Hong et al, 1996). The inherent¯exibility and tendency to oligomerize has made structural analysis of scaffolding proteins challenging.…”
Section: Introductionmentioning
confidence: 99%
“…The outer domain is presumably the C-terminal moiety, since the C terminus of the precursor should interact with the surface shell (7,21,36,44,45,69,71). We tentatively suggest that the linker may be an ␣-helical coiled coil, about four heptads (4 nm) long, based on scanning the SCMV assembly protein sequence (68) with a coiled-coil detection algorithm (40) (unpublished results).…”
Section: Discussionmentioning
confidence: 99%